Family Practitioners and Sexually Transmitted Diseases - Marc Steben (Canadian Journal of Infectious Diseases)
The family practitioner's role has traditionally been to maintain health with periodic examinations and to restore health in times of illness and injuries. Today. family practitioners are expected to play a more proactive role by assessing unexpressed patient needs. This new approach focuses on global knowledge of the patient, including lifestyle and workplace history. When assessing sexually transmitted diseases (STDs) in particular, it is important for the family practitioner to recognize the association of morality issues and to counsel without being judgemental. Primary prevention of STDs is aimed at reducing or eliminating risks before exposure occurs. and includes counselling on safe sex, condom use. substance abuse, needle/syringe use, and consideration of hepatitis B immunization and universal screening of pregnant women for hepatitis B surface antigen. Secondary prevention refers to the recognition and elimination (if possible) of an STD after exposure and includes early disease detection, adequate STD treatments, screening, human immunodeficiency virus testing with pre- and post test counselling, epidemiological treatment of patient contacts, and hepatitis B prophylaxis by passive or active immunization. Tertiary prevention is aimed at limiting disease progression or reversing damage, but such measures are usually quite expensive and of limited value. Assessment of risks for hepatitis B virus infection should include lifestyle indices such as sexual preference, sexual expression, number of partners and alcohol/drug consumption. Prostitutes, street youth and sexually abused individuals should be considered at high risk for hepatitis B virus infection. Counselling about hepatitis B virus infection involves risk evaluation, patient education, evaluation of immune status to hepatitis B virus and discussions about vaccine needs and availability.